Evidencialidad en la atribución copulativa: el caso de ser/estar claro - Cristian Valdez (Signo y seña, 1970)
This paper proposes a cognitive-functional account of the systematic differences between the constructions ser claro and estar claro. The use of these constructions is to be understood in the light of the semantic values of each of the verbs and in relation to the evidential dimension and the polysemy inherent to the adjective claro. A large sample of authentic oral occurrences has been analysed according to two parameters: the semantic category of the subject and the level of abstraction of the context. The results support the hypothesis that estar claro appears in contexts of direct evidence or inference, while ser claro categorizes information based on reasoning, general knowledge or conjecture.